Generic skills from qur'anic perspective - Siddig Ahmad, (Universiti Kebangsaan Malaysia, 2012)
Generic skills are defined as a set of skills that are directly related and needed for the working environment. Employers prefer to recruit officials who are competent in interpersonal communication, leadership skill, team work, oral and written skills. They are reluctant to employ graduates lacking certain necessary skills. This reveals the fact that there is a serious gap between the skills that are required by the employers and the skills that the graduates possess. Therefore, this research is focused on five aspects of generic skills namely; communication, team work, problem solving, lifelong learning and self-esteem. From Qur’anic perspective, the same terms have been used except minor differences in using various terms. The thematic approach is used when discussing these aspects from the Qur’an. The findings showed that the ways of effective communication are represented by terms of qawl sadid, qawl ma`ruf, qawl baligh, qawl maysur, qawl karim and qawl layyin. For collective work, ta`aruf and tafahum, as the pre-requisites, should be practiced via ta`awun and takaful. For problem solving, four methods are adapted from the Qur’an such as reflection of the past, observation, demonstration and asking questions. For lifelong learning, the establishment of learning institutions and the selfmotivation of learners are two pre-requisites that should be undertaken for its accomplishment. They could be practiced through open learning system, consultation and hands-on learning. Last but not least, for personality development could be built up through physical training, spiritual training and mental training.